Fe(III) Oxide-modified Indonesian Bentonite for Catalytic Photodegradation of Phenol in Water - Pradisty, Novia Arinda; Sihombing, Riwandi; Howe, Russell Francis; Krisnandi, Yuni Krisyuningsih (Makara Journal of Science, 2017)
Phenol, which is a major organic pollutant, is usually detected in industrial wastewater, and thus the wastewater should be processed further before discharged into water bodies. Application of heterogeneous catalysis using natural-basedmaterials is known to be effective and environmentallyfriendlyinremoving hazardous substances in water. In this study, local natural bentonite from the Tapanuli region in Indonesia was modified to eliminate dissolved phenol. Elimination by photodegradation reaction was conductedinaphoto-Fenton system utilizing Fe(III) oxide-modifiedbentonite (Fe-B) as catalyst. Fe-B was prepared byacation exchanging process using mixture solutions of NaOH and FeCl3 with OH/Femolar ratio of 2:1 and calcined at 300 °C. Material characterization was performed by X-ray diffraction (XRD), low-angle XRD, Fourier transform infrared spectroscopy and atomic absorption spectroscopy. The reaction components consisted of ultraviolet Clight, H2O2, and Fe-B, and they were processed in a batch reactor. The role of each component was analyzed by a series of reaction conditions (i.e., adsorption, photolysis, H2O2effect, Fenton, and homogeneous photo-Fenton). The heterogeneous photo-Fenton system was found to be essential for phenol degradation, as none of the reaction conditions caused total phenol removal in the 180 min reaction time. To conclude, heterogeneous photo-Fenton gave the highest photodegradation activity, and the best experimental condition for 1.10 mM phenol removal was 5 g L-1 catalyst, 78.35 mM H2O2, and 90 minreaction time.